Loss of TLR3 aggravates CHIKV replication and pathology due to an altered virus‐specific neutralizing antibody response - Zhisheng Her; Terk‐Shin Teng; Jeslin JL Tan; Teck‐Hui Teo; Yiu‐Wing Kam; Fok‐Moon Lum; Wendy WL Lee; Christelle Gabriel; Rossella Melchiotti; Anand K Andiappan; Valeria Lulla; Aleksei Lulla; et al. (EMBO Molecular Medicine)
Abstract RNA‐sensing toll‐like receptors (TLRs) mediate innate immunity and regulate anti‐viral response. We show here that TLR3 regulates host immunity and the loss of TLR3 aggravates pathology in Chikungunya virus (CHIKV) infection. Susceptibility to CHIKV infection is markedly increased in human and mouse fibroblasts with defective TLR3 signaling. Up to 100‐fold increase in CHIKV load was observed in Tlr3−/− mice, alongside increased virus dissemination and pro‐inflammatory myeloid cells infiltration. Infection in bone marrow chimeric mice showed that TLR3‐expressing hematopoietic cells are required for effective CHIKV clearance. CHIKV‐specific antibodies from Tlr3−/− mice exhibited significantly lower in vitro neutralization capacity, due to altered virus‐neutralizing epitope specificity. Finally, SNP genotyping analysis of CHIKF patients on TLR3 identified SNP rs6552950 to be associated with disease severity and CHIKV‐specific neutralizing antibody response. These results demonstrate a key role for TLR3‐mediated antibody response to CHIKV infection, virus replication and pathology, providing a basis for future development of immunotherapeutics in vaccine development.